Moringa (Moringa oliefera) Leaf Flour Addition on Water Content, Sensory Quality, Favorability Level, and Yield of Chicken Nuggets - S. Sulmiyati; Karolina Prihatiana Findyati; Bastari Sabtu (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2022)
Chicken nuggets are one fast food products made from processed chicken meat that can be processed using the innovation of adding moringa leaf flour to overcome the lack of vegetable fiber. This study aims to determine the water content, organoleptic quality, level of favorability, and yield of chicken nuggets with the addition of moringa leaf flour. The materials used were broiler chicken thigh and breast, moringa flour, wheat flour, kitchen spices (garlic, and pepper), salt, and binder (eggs, cornstarch, and breadcrumbs). The method used was a completely randomized design (CRD) with 4 treatments and 4 replications. The treatments consisted of P0; without the addition of Moringa leaf flour (control), P1; Moringa leaf flour 3%, P2; Moringa leaf flour 5%, and P3; Moringa leaf flour 7%. The variables observed were water content, organoleptic, favorability level, and yield. Data were analyzed using ANOVA and Kruskal-Wallis nonparametric test. The results showed that the best level of addition of Moringa leaf flour was 7% (P3) with a percentage decrease in water content of 56.89% and the highest at the addition of 3% (P1) at 59.52%, while the organoleptic value and level of favorability for chicken nuggets with the best addition of moringa leaf flour was in treatment P1 (3%) with a brownish yellow color, a slightly distinctive smell of nuggets and a slightly specific taste of nuggets. Judging from the results of the study, processing with the addition of moringa leaf flour can reduce the water content of chicken nuggets but it will affect the organoleptic quality of the panelists’ favorability for chicken nuggets if the addition of moringa leaf flour is above 3%.